The Use of TikTok Application to Improve Eleventh-Grade Students’ Speaking Skills - Tiara Z. Koping; Mochtar Marhum; Zarkiani Hasyim; Wahyudin Wahyudin (Journal of General Education and Humanities, 2025)
This study aimed to investigate the effect of using TikTok’s "Duet" feature on improving the speaking skills of eleventh-grade students. The research problem addressed the challenge of enhancing students’ English-speaking abilities through innovative digital media. A quasi-experimental research method with a pre-test and post-test design was applied to a sample of 44 students (n = 44) from the eleventh grade at SMA Labschool Untad Palu. The treatment involved using TikTok’s Duet feature as a learning medium during the speaking activities. The results showed a significant improvement in students’ speaking abilities (t = 6.21, p < 0.05) after the treatment, indicating the positive impact of the intervention. This significant improvement was observed in the accuracy, fluency, and comprehensibility aspects of speaking. The findings suggest that TikTok’s Duet feature can be an effective tool to support English-speaking skill development in high school students. However, the study has limitations, including the short duration of the treatment and the limited sample size. Further research is needed to assess the long-term effects of this intervention and to explore its applicability in diverse educational contexts.